Operational Optimization through the Development of a Digital Financial Transaction Recording Website in Village Owned Enterprise Sarwada Amerta, Taro Village: Optimalisasi Operasional melalui Pengembangan Website Pencatatan Transaksi Keuangan Digital di BUMDesa Sarwada Amerta Desa Taro - Kusuma, Tubagus Mahendra; Budaya, I Gede Bintang Arya; Pande, I Made Suandana Astika; Dharmendra, I Komang (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
In this community services activity, mentoring and implementation of a digital financial transaction recording system were conducted in village owned enterprise (VOE) Sarwada Amerta, Taro Village. The findings of this study demonstrate that the utilization of financial transaction information systems can optimize the financial operational processes of VOE. The efficiency and accuracy of financial data processing have improved, and the accessibility of financial information has become easier. However, it was found that the adaptation to the new information system still requires time for the human resources to consistently utilize the system. Strong support and commitment from relevant stakeholders, along with continuous educational efforts, are crucial factors in ensuring the successful implementation of the information system. This community services activity is expected to contribute to the economic development of the village through financial management education for VOE and by encouraging the utilization of information technology in local business financial management. Abstrak Pada kegiatan pengabdian masyarakat ini, dilakukan pendampingan dan implementasi sistem pencatatan keuangan digital di BUMDesa Sarwada Amerta, Desa Wisata Taro. Berdasarkan hasil dari kegiatan ini menunjukkan bahwa penggunaan sistem informasi pencatatan transaksi keuangan dapat mengoptimalkan proses operasional BUMDesa, khususnya dalam bidang keuangan. Efisiensi dan akurasi dalam pengolahan data keuangan meningkat, serta aksesibilitas informasi keuangan menjadi lebih mudah. Namun, ditemukan bahwa adaptasi terhadap sistem informasi yang baru masih memerlukan waktu bagi sumber daya manusia BUMDesa agar dapat menggunakan sistem dengan konsisten. Dukungan dan komitmen yang kuat dari pihak terkait, serta upaya edukasi yang berkelanjutan, menjadi faktor penting dalam memastikan keberhasilan implementasi sistem informasi ini. Kegiatan pengabdian ini diharapkan memberikan kontribusi dalam pengembangan ekonomi desa dengan edukasi manajemen keuangan BUMDesa serta mendorong pemanfaatan teknologi informasi dalam pengelolaan keuangan usaha di tingkat lokal.